Evaluation of SPARK C++ usability: modular programming for mechanical and civil engineering students - Azrina Suhaimi; Mohamad Faizal Ab Jabal; Harshida Hasmy; Azyan Yusra Kapi @ Kahbi (Journal of Computing Research and Innovation, 2024)
Technological innovations have transformed education, offering learning opportunities outside traditional classrooms through online resources. However, self-learning programming remains challenging for beginners. The SPARK C++ tool was developed to assist Mechanical and Civil Engineering students at Universiti Teknologi MARA in mastering C++ modular programming. This study evaluates the usability of SPARK C++ using Nielsen's metrics: learnability, efficiency, memorability, errors, and satisfaction. Sixty-three students from these engineering programs participated, providing data through Nielsen's Usability Test, which included Likert scale questions and open-ended feedback. The results revealed significant differences in usability perceptions by gender and program, with female Mechanical Engineering students reporting higher satisfaction. Key strengths were user-friendly design, engaging content, interactive quizzes, and multimedia features. Areas for improvement included better error messages, more comprehensive notes, and downloadable results. Enhancing these aspects can improve learning experiences and retention rates. This study highlights the need for continuous improvement of educational technologies based on user feedback and suggests future research should broaden usability testing to ensure inclusivity and adaptability.